Electrical Properties of Sub-1nm Diameter Silicon Nanowire Metal-Oxide-Semiconductor Device - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2025)
In this short communication, the electrical properties of a 0.7nm diameter Silicon nanowire metal-oxide-semiconductor device are theoretically calculated. The properties are: Intrinsic Fermi energy level in Si of the Silicon nanowire, conduction band offset at the oxide/Si interface, Fowler-Nordheim electron tunneling onset field, oxide leakage current density at the FN onset field, electrical breakdown field for a 10-4 A/cm2 oxide current density, electron and hole channel mobility, and total oxide/Si interface trap densities. It is considered that the SiNW MOSFET is the ultimate transistor for complementary MOS technology in Silicon.